ANALISIS PELAKSANAAN FUNGSI MANAJEMEN TERHADAP PENCAPAIAN INDIKATOR KEBERHASILAN PADA POSKESTREN DI PONDOK PESANTREN AN – NUR NGRUKEM BANTUL - chanif kurniasari (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2022)
One of the efforts to improve the role of Poskestren is to carry out management functions in accordance with the flow that has been determined by the health office to the performance of the management of Pesantren Health Post. At the Health Post Pesantren An-NurNgrukem, the problem was obtained, namely : There has been no training specifically for management, the knowledge of the manager about health is still lacking. health equipment is not complete, health workers are still lacking, and poskestren development strategy for the future is still unclear or there is no careful planning. Objective of this research is to know the success of Poskestren and the influence of the implementation of management functions on the achievement of success indicators in Poskestren An-Nur Ngrukem Bantul Yogyakarta year 2021. The research used is qualitative research method as a research procedure produced descriptive data, the sample used in the study is a purposive sampling technique where the research requires special criteria so that the samples taken later in accordance with the purpose of the research, as for the purposive sampling technique in the subject of this study are 4 informants poskestren an-NurNgrukem manager, data collection techniques namely observation, interview, documentation. Data analysis using data reduction, display/presentation of data and verification/conclusion. Based on research data that has been conducted by researchers, it can be stated that the success of poskestren in poskestren implementation guidelines is measured through 18 success indicators consisting of input indicators, process indicators and external indicators. Currently Poskestren An-nurNgrukem has reached 14 points of posketren success indicators, there are only 4 indicator points of success that can not be achieve. In the results of the study known Poskestren An-nurNgrukem is good enough in the implementation of the function of planning management, organizing, mobilization, and supervision in Poskestren it shows that one of the factors that influence the achievement of poskestren success indicators is the implementation of planning management functions , organizing, mobilizing, and supervising at Poskestren An-nurNgrukemBantul. That the implementation of the functions of planning management, organizing, mobilization, and supervision in poskestren An-NurNgrukem has been implemented quite well, the implementation of management functions affects the achievement of success indicators in Poskestren An-NurNgrukem, Bantul, Yogyakarta.